Changing Work Systems, Changing Social Relations? A Canadian General Motors Plant - Clarke, Louise (Relations industrielles / Industrial Relations, 1997)
This article presents some findings of an ethnographic case study on social relations in an existing vehicle assembly plant where the traditional drag chain has been replaced by Swedish automated guided vehicle technology and some aspects of Japanese work organization have been implemented. The findings challenge claims that Fordism is being replaced by a fundamentally new production model, and that this is resulting in more fulfilling work and cooperative social relations. There are many continuities with Fordism and highly contradictory social relations. This and other studies of new work Systems suggest, in fact, that contradictions between control and commitment, rather than being minimized or dissolved, can actually be heightened.